Evaluation of anti-inflammatory effects of green tea and black tea: A comparative in vitro study - Priyanka Chatterjee; Sangita Chandra; Protapaditya Dey; Sanjib Bhattacharya (Wolters Kluwer Medknow Publications, 2012)
The present study was conducted to evaluate and compare the anti-inflammatory effects of aqueous extracts of green tea and black tea leaves (Camellia sinensis) against the denaturation of protein in vitro. The test extracts at different concentrations were incubated with egg albumin under controlled experimental conditions and subjected to determination of absorbance to assess the anti-inflammatory property. Diclofenac sodium was used as the reference drug. The present results exhibited a concentration-dependent inhibition of protein (albumin) denaturation by both the tea extracts. From the present findings it can be concluded that both green and black tea leaves possessed a marked anti-inflammatory effect against the denaturation of protein, in vitro. Green tea was found to be more active than black tea, plausibly due to the higher flavonoid contents of green tea.